Application of the Reasons for Elimination of Criminals in Cases of Corruption - Ifrani Ifrani; Noor Reza Ihsan (Universitas Syiah Kuala, 2021)
The purpose of this study was to find out the application of the reasons for the elimination of criminals in cases of corruption. The results of this study are case number: 87/Pid.Sus/2010/PN.Mrb, which was strengthened in the Supreme Court's Cassation decision number: 321 K/Pid.Sus/2011, was wrong in applying the excuse of forgiveness as the reason for eliminating the crime in its legal considerations, where the element of forgiving reason applied by the Panel of Judges was not fulfilled, but the justifying reason should be applied because one of the elements of Article 3 of Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning the eradication of criminal acts of corruption was not fulfilled because it relied on legal facts and expert testimony without mentioning in detail and with certainty who was benefited from the act, so the implication in this case is that the defendant should be acquitted (vrisjpraak).